A comparative study of odorants for gas escape detection of natural gas and hydrogen. (19th April 2021) - Mouli-Castillo, Julien; Orr, Georgina; Thomas, James; Hardy, Nikhil; Crowther, Mark; Haszeldine, R. Stuart; Wheeldon, Mark; McIntosh, Angus
Abstract: Decarbonising the residential heating and cooking sector is essential to meet national and international carbon emission reduction targets. Hydrogen has been identified by the scientific community, industry, and policy makers as part of the solution to this challenge. Hydrogen has been used for decades in many industries, formerly making up approximately 50% of the Town Gas used for heating and cooking in UK homes in the mid 20th century. It is now crucial to ensure safety regulations are met, and public acceptance gained, before hydrogen can start being used for residential heating. Demonstration projects require hydrogen distribution networks to be odorised. This study examines the use of sulphur-based odorants, which are currently in use in the UK and Europe to odorise Natural Gas, to be used in a 100% hydrogen gas demonstration network in the UK. We undertook a comparative testing programme to evaluate the escape detection properties of odorised hydrogen against odorised methane and natural gas. This comparative approach will help address the question asked by UK and EU regulators: is hydrogen 'as safe as' natural gas? The results show that untrained participants can identify an escaping gas odorised with Odorant New Blend and standby odorant 2, in hydrogen, natural gas or methane, at the regulatory threshold of 1% gas in air. These results contribute to the safety-case of H100 led by SGN. Highlights: Odorant NB and THT in hydrogen, methane and natural gas (NG) are compared. The odorants tested with hydrogen allow for detection of gas escapes similar to NG. The comparative methodology aligns with the UK's Health and Safety Executive policy. The findings can support the development of hydrogen demonstration projects.